Impact of psychological factors on energy-saving behavior: Moderating role of government subsidy policy - Hong, J.; She, Y.; Wang, S.; Marinova, Dora (2019)
© 2019 Elsevier Ltd This study investigates the impact of government incentive measures on the energy-saving behavior of residents and the impact path. Previous literature has discussed the influencing factors of residents' energy-saving behavior but rarely considered the intrinsic relationship and interaction among those factors. Thus, this paper studies the effect of government incentive measures and the moderating effect of psychological factors on the energy-saving behavior of residents. Random questionnaires are used to obtain responses, followed by test analysis. Results show that the energy-saving attitude and environmental responsibility (ER) of residents have a significant positive impact on energy-saving behavior, whereas consumer values (CV) have none. This result differs from the findings of previous studies. The government subsidy policy has a vital role in promoting energy-saving behavior and a significant positive moderating effect on attitude and energy-saving behavior. However, it has a significant negative moderating effect on ER and energy-saving behavior. These interesting findings fill in some gaps in the literature and can provide good recommendations for governments to formulate and implement energy conservation and environmental protection policies.